2013
DOI: 10.1021/jm4008449
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Full Histone Deacetylase Inhibitory Profiling of Azumamides A–E as Well as β2- epi-Azumamide E and β3-epi-Azumamide E

Abstract: Cyclic tetrapeptide and depsipeptide natural products have proven useful as biological probes and drug candidates due to their potent activities as histone deacetylase (HDAC) inhibitors. Here, we present the syntheses of a class of cyclic tetrapeptide HDAC inhibitors, the azumamides, by a concise route in which the key step in preparation of the noncanonical disubstituted β-amino acid building block was an Ellman-type Mannich reaction. By tweaking the reaction conditions during this transformation, we gained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…24 Analogous to the reported protocol, diastereoselective Ellman-type Mannich reaction between 15 (S-auxiliary) and 16 afforded the desired R-isomer (17) in 58% isolated yield (dr = 77:23) as shown in Figure 2c. The absolute stereochemistry was determined by X-ray crystallography upon desilylation with Bu 4 NF to give 18.…”
Section: ■ Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…24 Analogous to the reported protocol, diastereoselective Ellman-type Mannich reaction between 15 (S-auxiliary) and 16 afforded the desired R-isomer (17) in 58% isolated yield (dr = 77:23) as shown in Figure 2c. The absolute stereochemistry was determined by X-ray crystallography upon desilylation with Bu 4 NF to give 18.…”
Section: ■ Resultsmentioning
confidence: 73%
“…24 In said study, we observed a detrimental effect on inhibitory potency when changing the stereochemistry of either chiral center in the β-amino acid residue (gray shading in Figure 1a). Although this drastic effect was not particularly surprising when changing the stereochemistry of the extended Zn 2+ -binding side chain, which must be projected into the active site, the importance of the stereochemistry of the methyl group was less predictable.…”
Section: ■ Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…5.14) is a cyclic tetrapeptide previously isolated in 1996 from the fungus, Fusarium pallidoroseum, and it was reported as an antimalarial agent [160]. Recent study revealed that the b-amino acid residue of azumamides has significant influence on the HDAC activities, and that azumamides C (92) and E (94) exhibited potent inhibitory activity of HDAC10 and HDAC11 [163]. Azumamides A-E (90-94) (Fig.…”
Section: Histone Deacetylase Inhibitors As Anticancer Agentsmentioning
confidence: 99%